Islamic Religious Education Learning in Value Development Religious Tolerance (Multicase Study of 1 Rambipuji Public Junior High School and St Peter's Catholic Junior High School Jember) - Hidayatillah, Nurul; Hakim, Lukman (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2022)
This research departs from the phenomenon of rampant intolerance in Indonesia, rampant issues of SARA, brawl between students, discrimination between majority and minority because of the lack of understanding tolerance. Learning Islamic Religious Education is one means to disseminate the importance of understanding religious tolerance to students.The focus of research in this thesis are: (1) How to Study Islamic Religious Education (PAI) in developing student humanist value in State Junior High School 1Rambipuji and Catholic Junior High School St. Petrus Jember?; (2) How to study Islamic Education (PAI) in developing pluralist values of students at State Junior High School 1Rambipuji and Catholic Junior High School St. Petrus Jember?; (3) How to study Islamic Education (PAI) in developing the democratic value of students at State Junior High School 1Rambipuji and Catholic Junior High School St. Petrus Jember? This thesis uses descriptive qualitative approach with case study type research with multi case design. Data collection techniques through observation, interview and documentation. Researchers analyzed data with multi-case analysis of individual and cross site case analysis. Data validity using source triangulation. The findings show: First, PAI learning in the development of democratic, humanist and pluralist values at Rambipuji 1 Junior High School is the development in the classroom with PAI learning materials. From Class VII material as in the 2013 curriculum syllabus, class VIII is in the curriculum syllabus of KTSP, class IX as in the curriculum of the KTSP curriculum. While in St. Petrus Jember Middle School uses 18 character guidelines. The development of democratic values is also realized by bringing in teachers in accordance with the students 'religion, the activity of choosing class leaders and the student council leader in a democratic manner regardless of students' backgrounds, so that each student has the right to be chosen, besides that students are entitled to follow the talents and interests they want as self-development. The development of humanist values is also realized through social service activities, darling and scouts. The development of pluralistic values is realized by halal bil halal, the prohibition on eating is arbitrarily found during the holy month and praying according to the religion of each of them when steamala or before learning begins